Penerapan Pembelajaran Kontekstual untuk Menumbuhkan Kepedulian Lingkungan pada Siswa Kelas I melalui Pendidikan Pancasila - Putri Prilin, Roofisyha Anggel; Dewi, Afni Khalistania; Ulfah, Eka Aslamiyah; Widodo, Susilo Tri (YASIN, 2025)
Although environmental concern among elementary school students has been widely studied, research that specifically highlights the integration of contextual learning in Pendidikan Pancasila for Grade 1 students remains very limited. This study aims to evaluate the effectiveness of contextual learning in fostering environmental concern among Grade 1 elementary school students. A qualitative approach with a single case study design was employed, involving 20 participants selected through purposive sampling. Data were collected through observation, interviews, documentation, and field notes, and were analyzed using thematic analysis techniques. The findings show that contextual learning significantly enhances students’ awareness of cleanliness, their engagement in caring for the environment, and their ability to relate the values of Pancasila to concrete actions in daily life. These results contribute to the development of constructivist learning theory and broaden the understanding of character education implementation at the early elementary level. The study concludes that contextual learning is a key strategy for shaping environmentally responsible behavior and recommends that teachers design real-life-based activities within Pendidikan Pancasila lessons. The implications of this research include theoretical contributions to the character education literature and practical recommendations for educational institutions in designing meaningful learning, while also opening opportunities for further research on the application of contextual learning at different educational levels.